Perspectives of Employees’ Home Office in the Slovak Republic in the Context of the COVID-19 Pandemic - Silvia BARNOVA; Slavka KRASNA (Communications of International Proceedings, 2022)
The COVID-19 pandemic has brought several lockdowns worldwide, which has caused that most organizations has had to move their offices into their employees’ households and so, flats and houses have become workplaces. At the time of writing the proposed paper, i.e. more than two years after the outbreak of the pandemic crisis, based on the newly gained experiences, several conclusions regarding the benefits and shortcomings of working from home can be made. Those can serve as a basis for making decisions regarding the way of organizations’ functioning as well as further development in the field of using workplaces by organizations. In the proposed study, the notions of “home office” and “telework” are defined, an overview of the legislative aspects of home office is provided, and the current situation in Slovakia is described. In the final part of the paper, opportunities for the application of home office in the future are dealt with.
Keywords: home office; telework; Labour Code; COVID-19